Preliminary assessment of age- and sex-related differences in brain volume using Quantib™ brain quantification: a study in a Vietnamese cohort - Dang Luu Vu; Dang Luu Vu; Thi Phuong Lien Do; Khoi Viet Nguyen; Huu An Nguyen; Huu An Nguyen; Quang Anh Nguyen; Quang Anh Nguyen; Van Khang Le; Van Khang Le; Ngoc Trang Nguyen; Hong Khoi Vo; et al. (Frontiers in Neurology)
ObjectiveThis study evaluates age- and sex-related differences in brain volume, including normalized gray matter (nGM), normalized white matter (nWM), cerebrospinal fluid (CSF) volume, and total intracranial volume (TIV) in cognitively normal adults using automatic volume segmentation on 3.0 Tesla MRI.MethodsA prospective cross-sectional study conducted from October 2021 to September 2022 included 110 cognitively normal participants. They were divided into younger (18–35 years) and older (60–80 years) groups. Brain MRI were performed at Bach Mai Hospital, and volumetric analysis utilized automated segmentation software (Quantib™ Brain, GE Healthcare). Differences in brain volumes were analyzed by age and sex.ResultsThe younger group comprised 57 participants (30 females, 27 males; mean age 28), and the older group comprised 51 participants (32 females, 19 males; mean age 66). nGM was significantly higher in younger than older groups (p < 0.001), with no significant sex differences (p = 0.51). nGM showed an inverse correlation with age in younger males (r = −0.56, p < 0.001) and older males (r = −0.52; p = 0.02), but not in females (p = 0.77 in younger group and p = 0.07 in older group). nWM was also higher in younger groups (p = 0.02), with no significant sex differences (p = 0.10) or correlation with age across all groups (p > 0.05). CSF volume was significantly higher in males (p = 0.001) and older groups (p < 0.001). A positive correlation was noted between CSF volume and age in younger males (r = 0.41; p = 0.02), but not in other groups. TIV was higher in males (p < 0.01) and in younger groups (p < 0.001), with no correlation with age in any group (p > 0.05).ConclusionThis preliminary study suggests potential age- and sex-related differences in brain volume indices among cognitively normal Vietnamese adults. Additional studies with larger and more representative populations are warranted to confirm and expand upon these findings.